THE IDEA OF MAHMUD YUNUS TO REFORM ARABIC TEACHING - Eka Srimulyani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
In Indonesian Islamic education, Mahmud Yunus is an educationalist who is full of idea and discourse to reform the Islamic education. Moreover, as the one who get involved in Religious department bureaucracy and other structural positions in Islamic institution, including his last career as the first rector of Imam Bonjol Islamic Institution of Padang, Mahmud Yunus has some chances to manifest his idea and discourse widely through his positions. If we try to analyze his idea on reformation in education and teaching, we can clearly see that he has put serious attention to Arabic Language and Arabic teaching. He has written many books such as Arab-Indonesia Dictionary (Qamus), Arabic Language Textbook, called Durus al-Lughah al-‘Arabiyyah, and a special book about Arabic Teaching.